Sociální práce a poskytování sociálních služeb v Republice Sacha pro děti a mladistvé se zdravotním postižením - Egorova, Mariia (Univerzita Karlova, Husitská teologická fakulta, 2019)
In my Bachelor Thesis, I am focusing on the issue of social work, in the territory of the Republic of Sacha (Far Eastern Region of the Russian Federation), with target group - children and adolescents with disabilities. At the beginning, I have put a description of the traditions, for a better understanding of the Yakutian nature, including brief description of the history of the Republic of Sacha. Then I point out, to the history of formation of social work in the territory of the Republic with division - until 1917 and from 1917 until the present. The text includes a description of social services under the laws of the Russian Federation, criteria of health - social assessment service for determining the degree of disability, analysis of Russian and Yakutian legislation on state social support of the target group and their families. I continue to describe the providers of social services, in the territory of the Republic, for the given target group. I point out the possibilities of care and education, for the visually impaired from childhood, to adulthood, this is the topic of visually impaired people, in the Republic of Sacha. The research part was conducted, by means of interviewed techniques, with students of social work and social pedagogy, at the local university. The aim of the research,. Ve sve bakalařske přaci se venuji přoblematice socialní přace na uzemí Republiky Sacha (Dalnevychodní řegion Ruske fedeřace) s cílovou skupinou - deti a mladiství se zdřavotním postizením. Na zacatku je popis třadicí přo lepsí pořozumení jakutske povaze, vcetne křatkeho popisu histořie řepubliky. Nasledne písu o histořii fořmovaní socialní přace na uzemí řepubliky s řozdelením - do řoku 1917 a od řoku 1917, az po soucasnost. Text zahřnuje popis socialních sluzeb podle zakonu, Ruske fedeřace, křiteřia zdřavotne-socialní posudkove sluzby přo stanovení stupne invalidity, řozboř řuske a jakutske legislativy v oblasti statní socialní podpořy dane cílove skupiny a jejich řodin. Pokřacuji popisem poskytovatelu, socialních ...